PENGARUH ATRIBUT PRODUK TERHADAP KEPUTUSAN PEMBELIAN - Yulasmi, Yulasmi (Jurnal Ekobistek, 2014)
This research aim to determine the extent of the effect of product attributes on purchase decisions. The variables used in this study is the variable Brand (X1), Quality (X2), Packaging (X3) and the Purchase Decisions (Y). The research method used was descriptive analysis, validity, reliability, correlation, regression with data collection techniques through the distribution of questionnaires, interviews and literature study as well as data processing by using the tools of the program SPSS version 18.0.The result showed that the variable Brands (X1) has a regression coefficient (B) 0, 214 with a significant level of 0.000 <0.05, H0 is rejected, Ha accepted, meaning there is significant influence between variables brand purchase decision. Variable Quality (X2) has a regression coefficient (B) 0, 597 with a significant level of 0.000 <0.05, H0 is rejected, Ha accepted, meaning there is significant influence between the variable quality of the purchase decision. Variable Packaging (X3) has a regression coefficient (B) 0, 111 with significant levels of 0, 099> 0.05, H0 is accepted, Ha rejected a partial means there is no significant effect of the variable quality of the purchase decision. For the R value is equal to 0.869, which means there is a strong positive relationship between brands (X1), Quality (X2), and Packaging (X3) with Purchasing Decisions (Y) and the coefficient of determination or R-square is 0.755, which means that the contribution of the brand , quality and packaging of the Buying Decision (Y) equal to 75.5% or 24.5% influenced by other variables not included in the studied variables. Keywords: Attributes Product, Purchase Decision